Insights Regarding Students Perception of the Teacher Role and the Process of Teaching - Case Study - Oana Badea (Social Sciences and Education Research Review)
This study explores students' perceptions of their teacher's role and teaching process. The learner-centered model is discussed in the context of teaching Romanian to foreign medical students. A case study of 56 students using a questionnaire is presented, analyzing their feedback on various aspects of the teaching process, including clarity of explanations, setting of standards, engagement, and use of time. The results indicate high overall student satisfaction, with minor areas identified for improvement.